2016
DOI: 10.4300/jgme-d-15-00201.1
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electronic Health Record Simulation to Understand the Accuracy of Intern Progress Notes

Abstract: Background With the widespread adoption of electronic health records (EHRs), there is a growing awareness of problems in EHR training for new users and subsequent problems with the quality of information present in EHR-generated progress notes. By standardizing the case, simulation allows for the discovery of EHR patterns of use as well as a modality to aid in EHR training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…Even more interesting was the difference in actual “note” elements between scribes. This is consistent with findings from studies showing discrepancies between physicians in the content and quality of documentation in notes [ 19 , 20 ]. Thus, whereas this phenomenon is most likely not unique to scribes, it does imply that scribes may face the same issues that are found among other clinicians.…”
Section: Discussionsupporting
confidence: 92%
“…Even more interesting was the difference in actual “note” elements between scribes. This is consistent with findings from studies showing discrepancies between physicians in the content and quality of documentation in notes [ 19 , 20 ]. Thus, whereas this phenomenon is most likely not unique to scribes, it does imply that scribes may face the same issues that are found among other clinicians.…”
Section: Discussionsupporting
confidence: 92%
“…Feedback efforts, therefore, while highly emphasized in medical education, may fail if they lack such contextual credibility. For example, March, et al (2016) showed a wide variability in intern's clinical documentation even when using a simulated exercise that closely approximated clinical care [12]. In keeping with the behaviors of complex adaptive systems, perhaps our intervention fell short due to the residents' relatively low perceived importance associated with clinical documentation, the many competing demands on trainee time, and minimal incentive to create documentation that is accurate and of high quality.…”
Section: Lessons Learnedmentioning
confidence: 93%
“…On the other hand, one of the disadvantages attributed to the EHR is that it allows "copy & paste" of previous records, duplicating information and perpetuating possible errors. This functionality has appeared in the literature related to saving time, increasing the efficiency of the process (Al Hadidi et al, 2017;Hartzband and Groopman, 2008;Heiman et al, 2014;Hirschtick, 2006;March et al, 2016;Shoolin et al, 2013). Transcriptions should be made in a conscious and responsible way by health professionals, taking advantage of the positive points for which "copy & paste" was created.…”
Section: Phrs Compared To Ehrsmentioning
confidence: 99%